PENGAWASAN KENDARAAN TRUK BERTONASE BERAT DI JALAN UMUM KOTA PEKANBARU - Gesaki Daitia Anugerah; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Supervision of heavy-duty truck controls aimed at maintaining road hygiene, as well as public road safety and security. Supervision is conducted on the compliance of the obligations of licensees / users of heavy truck vehicles in accordance with the provisions of local regulations related to the use of public roads. However, in the implementation of surveillance is still the discovery of trucks in violation of the obligation to use road or overcrowded trucks or heavy truckloads that violate the provisions of the time lap.In this research, the theoretical concept used is the theory of supervision proposed by Brantas (2009) as a research instrument, in which to measure the monitoring of heavy truck loaded vehicles there must be a standard of supervisory work, further action assessment on the results achieved and improvement actions if deviate from the standard (defined conditions). This research uses qualitative descriptive method with data collection techniques including interview, observation and documentation study.The result of the research shows that the monitoring of heavy truck vehicles has not been optimally implemented. Where the assessment measures have not achieved results in accordance with the objective of the captive and the regulation of the liability of road use, such as the presence of heavy truck vehicles that violate the road routes, the vehicles that do not use tarpaulins, and the liability of road users for heavy truck vehicles, improvements by applying sanctions for heavy truck vehicles users have not been firmly implemented, sanctions given warnings and fines, while against unloading of overload has not been carried out. Low control factors for heavy truckloaded vehicles include the ability of supervisory officers, who are in the surveillance post, lack of monitoring posts and supporting infrastructure, and coordination between the Transportation Agency and the Pekanbaru Traffic Police Unit not yet scheduled / synergic, the coordination tends to be kesadarn officer in the field.Key Words: Supervision, Road Usage Arrangement, Road Trip, Heavy Bertonase Trucking Vehicle